Experimental investigation of rubberized reinforced concrete continuous deep beams - Ali Abdulameer Kadhim; Hayder Mohammed Kadhim (Journal of King Saud University: Engineering Sciences)
Results of fourteen two-span continuous deep beams made from ordinary reinforced concrete (ORC) as a reference and rubberized reinforced concrete (RRC) is presented and discussed in this research. The main parameters are the rubber ratios as a replacement with coarse and fine aggregate and the shear span/depth ratio (a/h) is 1.33 and 1.66. Chip and crumb rubbers were used to replace coarse and fine aggregate respectively in four different amounts by volume (5%, 10%, 15%, and 20%). The proposed mix shows an ability to replace 20% of the aggregate (coarse or fine), and the production is still structural concrete. All beams design to fail in shear. The main crack is formatted between the intermediate support and the applied load diagonally. In spite of the inclusion of waste tire rubber in concrete having specific apparent degradations, the potential benefit seems to overlook the adverse effects and also provides the primary significant value of resolution for rubber waste problems. The results show that 20% volumetric substitution of natural coarse or fine aggregates with tier rubber reduced the ultimate load of continuous deep beams by 32.06% and 32.65% but significantly increases the ultimate deflection by 83.07% and 106.28% respectively. The ductility of rubberized continuous deep beams increased up to 36.95% when the replacement ratio of crumb rubber is 20%.